The performing pianist's guide to fingering - Banowetz, Joseph; Fowke, Philip; Harper, Nancy Lee (Indiana University Press, 2021)
"The Performing Pianist's Guide to Fingering, the much-anticipated companion to Joseph Banowetz's The Pianist's Guide to Pedaling, provides practical fingering solutions for technical musical passages. Banowetz contends that fingering choices require much thought and consideration and that too often these choices are influenced by historical traditions and ideas rather than by actual performance conditions. By returning to the unedited original compositions, he strives to help the advanced pianist think through the composer's musical intent and the actual performance tempo and dynamics when selecting the fingering. Banowetz also includes valuable contributions by Philip Fowke, who examines redistributions by Benno Moiseiwitsch in Rachmaninoff's compositions, and Nancy Lee Harper, who explores the often very different approaches to fingering found in keyboard music of the Baroque era. The Performing Pianist's Guide to Fingering will be useful to the advanced pianist and to instructors looking to guide students in improving this important art"--